Análise da degradação de terras na bacia hidrográfica do rio Lifidzi no Planalto de Angónia, província de Tete – Moçambique - Mandala, Sabil Damião; Simão, Isidro Alexandre; Macamo, Laurinda Milagre; Caetano, Ali José Santos; Uiliamo, Eza Bento; Massuanganhe, Edna Aminosse (Geopauta, 2024)
Land degradation is one of the biggest global environmental problems facing humanity today. Human activities that cause land degradation include: tree felling, burning, inadequate agricultural practices, among others. The research aimed to develop a land degradation and risk map, on a scale of 1: 250,000, of the Lifidzi River basin, using geoprocessing in QGIS and ARGIS, with a weighted analysis of the parameters of the natural and cultural environment, seeking to measure the occurrence of land degradation in the study area. The choice of this river basin was due to its pedological and climatic peculiarities, high population density and scarcity of studies of this nature in this district. As a result, it was possible to carry out a qualitative and quantitative analysis of the anthropogenic influence on land degradation in the basin.